Los efectos procesales de la mala fe negocial declarada en un arbitraje potestativo - Soltau Salazar, Sebastián (2014)
The facultative arbitration in labor matters procedures allows either party of   the employment relationship to compel the other to submit their disputes to an arbitral tribunal. One of the application assumptions of the facultative arbitration in labor mattersprocedures when bad faith of a party during the negotiation of the statement is noticed,which should be tested.What happens with the decision of the Arbitral Tribunal which admits the claim and establishes that it has jurisdiction to hear the case? In this article, the author analyzes the procedural effects of this decision, in the light of the doctrine and jurisprudence.